Development of Intelligent Multi-agents System for Collaborative e-learning Support - Issam Matazi; Rochdi Messoussi; Salah-Eddine Bellmallem; Ilham Oumaira; Abdellah Bennane; Raja Touahni (Institute of Advanced Engineering and Science, 2018)
The aim of this paper is the introduction of intelligence in e-learning collaborative system. In such system, the tutor plays an important role to facilitate collaboration between users and boost less active among them to get more involved for good pedagogical action. However, the problem lies in the large number of platform users, and the tutor tasks become difficult if not impossible. Therefore, we used fuzzy logic technics in order to solve this problem by automating tutor tasks and creating an artificial agent. This agent is elaborate in basing on the learners activities, especially the assessment of their collaborative behaviors. After the implementation of intelligent collaborative system by using Moodle platform, we have tested it. The reader will discover our approach and relevant results.